2005
DOI: 10.1038/nn1510
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p75NTR by proBDNF facilitates hippocampal long-term depression

Abstract: Pro- and mature brain-derived neurotrophic factor (BDNF) activate two distinct receptors: p75 neurotrophin receptor (p75(NTR)) and TrkB. Mature BDNF facilitates hippocampal synaptic potentiation through TrkB. Here we report that proBDNF, by activating p75(NTR), facilitates hippocampal long-term depression (LTD). Electron microscopy showed that p75(NTR) localized in dendritic spines, in addition to afferent terminals, of CA1 neurons. Deletion of p75(NTR) in mice selectively impaired the NMDA receptor-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
616
3
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 722 publications
(664 citation statements)
references
References 50 publications
39
616
3
6
Order By: Relevance
“…Furthermore, this noncompetitive NMDA antagonist disrupts synaptic plasticity in the amygdala (Bauer et al, 2002). Of particular relevance to the present argument is the fact that NMDA NR2B receptor activation is required for the induction of LTD in vitro under some circumstances Liu et al, 2004;Woo et al, 2005;Izumi et al, 2006; but see Hendricson et al, 2002;Morishita et al, 2007) and for NMDA-induced AMPA receptor endocytosis in cultured neurons (Kim et al, 2001;Tigaret et al, 2006). Indeed, recent studies have demonstrated that systemic administration of Ro 25-6981 at the same dose used in the present study blocked selectively the induction of LTD while having no effect on LTP in the hippocampus in vivo (Fox et al, 2006;Wong et al, 2007).…”
Section: Manipulations That Disrupt Ltd Formation Disrupt Fear Extincmentioning
confidence: 69%
“…Furthermore, this noncompetitive NMDA antagonist disrupts synaptic plasticity in the amygdala (Bauer et al, 2002). Of particular relevance to the present argument is the fact that NMDA NR2B receptor activation is required for the induction of LTD in vitro under some circumstances Liu et al, 2004;Woo et al, 2005;Izumi et al, 2006; but see Hendricson et al, 2002;Morishita et al, 2007) and for NMDA-induced AMPA receptor endocytosis in cultured neurons (Kim et al, 2001;Tigaret et al, 2006). Indeed, recent studies have demonstrated that systemic administration of Ro 25-6981 at the same dose used in the present study blocked selectively the induction of LTD while having no effect on LTP in the hippocampus in vivo (Fox et al, 2006;Wong et al, 2007).…”
Section: Manipulations That Disrupt Ltd Formation Disrupt Fear Extincmentioning
confidence: 69%
“…Recent work suggests that BDNF is released in 'pro-forms' (estimated at 19-34 kD) that are cleaved to generate mature, 13-14 kD BDNF. Both pro-and mature BDNF proteins can mediate neurotrophin signaling but the mature form is argued to be the variant that supports LTP and neuronal viability (Pang et al, 2004;Lu et al, 2005;Woo et al, 2005). Because ELISA studies so far reported used antisera that detect both pro-and mature BDNF proteins, it is possible that age-related changes in the latter, LTP-related form of the neurotrophin, were obscured by relatively stable levels of its larger precursor.…”
Section: Causes Of Age-related Changes In Synaptic Plasticitymentioning
confidence: 99%
“…This isoform is not further processed into mBDNF and its function has not been elucidated yet. According to the "Ying and Yang" hypothesis (Lu et al, 2005), both mBDNF and proBDNF have particular neurobiological properties. In particular, proBDNF regulate neuronal survival Koshimizu et al, 2009;Woo et al, 2005) and boosts synaptic pruning whereas mBDNF improves the differentiation of new neurons.…”
Section: The Role Of Probdnf In Patients With Schizophreniamentioning
confidence: 99%
“…According to the "Ying and Yang" hypothesis (Lu et al, 2005), both mBDNF and proBDNF have particular neurobiological properties. In particular, proBDNF regulate neuronal survival Koshimizu et al, 2009;Woo et al, 2005) and boosts synaptic pruning whereas mBDNF improves the differentiation of new neurons. Also, the conversion of proBDNF into mBDNF seems to be decisive for signal transmission and synaptic plasticity.…”
Section: The Role Of Probdnf In Patients With Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation